Extension of RBE-weighted 4D particle dose calculation for non-periodic motion. (November 2021) - Steinsberger, Timo; Alliger, Christian; Donetti, Marco; Krämer, Michael; Lis, Michelle; Paz, Athena; Wolf, Moritz; Graeff, Christian
Highlights: Implemented RBE-weighted 4D particle dose alculation for irregular motion. Enables dose calculations on arbitrarily long series of CT images. Impact of irregular motion studied on simulated human phantom CT sequences. Experimental validation of dose calculation algorithm with moving IC array detector. Will enable exploration of effects and study of motion mitigation strategies. Abstract: Purpose: Highly conformal scanned Carbon Ion Radiotherapy (CIRT) might permit dose escalation and improved local control in advanced stage thoracic tumors, but is challenged by target motion. Dose calculation algorithms typically assume a periodically repeating, regular motion. To assess the effect of realistic, irregular motion, new algorithms of validated accuracy are needed. Methods: We extended an in-house treatment planning system to calculate RBE-weighted dose distributions in CIRT on non-periodic CT image sequences. Dosimetric accuracy was validated experimentally on a moving, time-resolved ionization chamber array. Log-file based dose reconstructions were compared by gamma analysis and correlation to measurements at every intermediate detector frame during delivery. The impact of irregular motion on treatment quality was simulated on a virtual 4DCT thorax phantom. Periodic motion was compared to motion with varying amplitude and period ± baseline drift. Rescanning as a mitigation strategy was assessed on all scenarios. Results: In experimental validation, average gamma pass rates were 99.89+-0.30% for 3%/3 mm and 88.2+-2.2% for 2%/2 mm criteria. Average correlation for integral dose distributions was 0.990 ± 0.002. Median correlation for single 200 ms frames was 0.947 ± 0.006. In the simulations, irregular motion deteriorated V95 target coverage to 81.2%, 76.6% and 79.0% for regular, irregular motion and irregular motion with base-line drift, respectively. Rescanning restored V95 to > 98% for both scenarios without baseline drift, but not with additional baseline drift at 83.7%. Conclusions: The validated algorithm permits to study the effects of irregular motion and to develop and adapt appropriate motion mitigation techniques.